AN ANALYSIS OF FLOUTING MAXIM BY MAIN CHARACTER IN FREEDOM WRITERS MOVIE WRITTEN BY RICHARD LaGRAVANESE - Mariati Mariati (Pendekar: Jurnal Pendidikan Berkarakter, 2018)
Flouting Maxim is intentionally breaking the maxim to convey the hidden meaning and the listener is expected to be able to catch the hidden meaning. In conversation,sometimes people are uncooperativeby breaking the maxim so that it occursmisunderstanding. Therefore, the researcher was interested to analyze flouting maxim by main character in Freedom Writersmovie written by Richard LaGravanesein order to find the types of flouting maxim by using qualitative research and the data were collected through the movie script especially from main character’s utterance which named Erin. Based on findings of the study, the researcher found four flouting maxims such as the flouting maxim of quantity reaches the highest number with 34 data (33.4%) which implied that the main character in the movie gave too little and too much information which was not required,the flouting maxim of relation reaches the second highest number with 29 data (28.4%) which implied that the main character gave the irrelevant utterance and controlled the conversation by changing the topic of conversation, the flouting maxim of quality reaches the third number with 25 data (24.5%)which implied that the main character said which was believed to be false and lacked adequate evidence andthe flouting maxim of manner reaches the lower number with 14 data (13.7%) which implied that the main character in the movie gave ambiguous, unnecessary prolixity and didn’t avoid obscurity.Flouting Maxim is intentionally breaking the maxim to convey the hidden meaning and the listener is expected to be able to catch the hidden meaning. In conversation,sometimes people are uncooperativeby breaking the maxim so that it occursmisunderstanding. Therefore, the researcher was interested to analyze flouting maxim by main character in Freedom Writersmovie written by Richard LaGravanesein order to find the types of flouting maxim by using qualitative research and the data were collected through the movie script especially from main character’s utterance which named Erin. Based on findings of the study, the researcher found four flouting maxims such as the flouting maxim of quantity reaches the highest number with 34 data (33.4%) which implied that the main character in the movie gave too little and too much information which was not required,the flouting maxim of relation reaches the second highest number with 29 data (28.4%) which implied that the main character gave the irrelevant utterance and controlled the conversation by changing the topic of conversation, the flouting maxim of quality reaches the third number with 25 data (24.5%)which implied that the main character said which was believed to be false and lacked adequate evidence andthe flouting maxim of manner reaches the lower number with 14 data (13.7%) which implied that the main character in the movie gave ambiguous, unnecessary prolixity and didn’t avoid obscurity.